Subarachnoid hemorrhage - a Bayesian approach to a neurological black swan - Bedolla, John (Henry Stewart Talks, 2018)
Bayes theorem, Spontaneous subarachnoid hemorrhage, Bayesian approach, Pretest probability SAH in headache, Actionable clinical data to adjust pretest, Bayesian pretest inferences, Fagan nomogram CT before/after 6 hours, Who still needs an LP?, Ottawa subarachnoid hemorrhage rule